Mobility of students and quality of higher education: An empirical analysis of the "Unified Brain Drain" model - Elise S. Brezis; Ariel Soueri (Bar-Ilan University, Department of Economics, 2013)
Globalization has led to a vast flow of migration of workers but also of students. The purpose of this paper is to analyze the migration of individuals encompassing decisions already at the level of education. We present a unified brain drain model that incorporates the decisions of an individual related to migration vis-à-vis both education and work. In the empirical part, this paper addresses international flows of migration within the Bologna Process and presents strong evidence of concentration of students in countries with high-quality education.
Keywords: F22; I23; J24; 330; Brain drain; Globalization Higher education; Human capital; Migration; Mobility; Bologna process